Kratom (Mitragyna speciosa) dependence, withdrawal symptoms and craving in regular users - Singh, Darshan; Müller, Christian P.; Vicknasingam, Balasingam K. (Drug and Alcohol Dependence, 2014)
Kratom (Mitragyna speciosa) preparations have been traditionally used in Southeast Asia for its medicinal properties. Lately, Kratom use has spread to Europe and the US, where abuse potential and health hazards increasingly emerge. This study is the first to measure systematically Kratom dependence, withdrawal symptoms, and drug craving in regular Kratom users in Malaysia.A cross-sectional survey of 293 regular Kratom users was conducted in the community across three northern peninsular states of Malaysia. The Leeds Dependence Questionnaire, Marijuana Withdrawal Checklist, and Marijuana Craving Questionnaire-Short Form were used to measure Kratom dependence, withdrawal and craving.More than half of the regular users (>6 month of use) developed severe Kratom dependence problems, while 45% showed a moderate Kratom dependence. Physical withdrawal symptoms commonly experienced include muscle spasms and pain, sleeping difficulty, watery eyes/nose, hot flashes, fever, decreased appetite, and diarrhoea. Psychological withdrawal symptoms commonly reported were restlessness, tension, anger, sadness, and nervousness. The average amount of the psychoactive compound, mitragynine, in a single dose of a Kratom drink was 79mg, suggesting an average daily intake of 276.5mg. Regular users who consumed >=3 glasses Kratom per day, had higher odds of developing severe Kratom dependence, withdrawal symptoms, and inability to control Kratom craving.The findings from this study show that regular Kratom use is associated with drug dependency, development of withdrawal symptoms, and craving. These symptoms become more severe with prolonged use and suggest a stronger control of the drug.
EVALuna2:23655